1981
DOI: 10.1002/art.1780240503
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of cervical atypia in women with systemic lupus erythematosus treated with chemotherapy

Abstract: In a retrospective study we found that 19 of 80 women with systemic lupus erythematosus had atypical cervical smears as compared to only 9 of 80 agematched women without the disease. This increased incidence occurred mainly among women receiving cytotoxic drugs. Cervical atypia in women with lupus was not morphologically different from cervical atypia in general. Possible mechanisms responsible for the increased incidence are discussed. It is concluded that women with lupus who receive chemotherapy should have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1
1

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 23 publications
0
50
1
1
Order By: Relevance
“…16 The cytologic features of nuclear and cellular enlargement, polychromasia, binucleation and multinucleation, nuclear wrinkling, cytoplasmic fibrils and granules, vacuolization and bizarre forms have been described. 29 Conflicting results regarding the presence or absence of squamous and glandular atypia 5,12,23,25 have been documented. In some cases, the precise degree of squamous atypia is uncertain since the Papanicolaou classification was used.…”
mentioning
confidence: 99%
“…16 The cytologic features of nuclear and cellular enlargement, polychromasia, binucleation and multinucleation, nuclear wrinkling, cytoplasmic fibrils and granules, vacuolization and bizarre forms have been described. 29 Conflicting results regarding the presence or absence of squamous and glandular atypia 5,12,23,25 have been documented. In some cases, the precise degree of squamous atypia is uncertain since the Papanicolaou classification was used.…”
mentioning
confidence: 99%
“…This was not in agreement with the results of this study. Another report found that in women currently receiving azathioprine, 50% had cervical atypia compared with 11% of controls (20) .…”
Section: Discussion:-mentioning
confidence: 97%
“…4], The median duration of SLE, as measured from onset to the most recent follow-up. was longer in patients who devel oped tumors than in those without malignancies (16.1 vs. 11 years) [1], The incidence of malignancy may be enhanced by the presence of SLE [3], Moreover, the higher incidence of malignancy in patients with SLE reflects the high rate among those treated with immuno suppressive drugs [4], Problems exist in the treatment of patients with ad vanced cervical cancer and SLE. First, patients with SLE usually are in poor general condition, with complications of renal dysfunction and poor wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports of malignancy in patients with systemic lupus erythematosus (SLE) [1,2], Malignant lymphoma is the malignancy most commonly discussed in relation to SLE [3], However, there are a few reports of cervical cancer with SLE, although an increased incidence of cervical atypia has been reported in patients with SLE [4], The present report describes a case with a 20-year his tory of SLE who developed advanced cervical cancer. In addition, clinical course of the rash is discussed in rela tion to the local immune response.…”
Section: Introductionmentioning
confidence: 90%